MAGNETIC STRATIGRAPHY OF THE SCAGLIA ROSSA: IMPLICATIONS FOR SYNDEPOSITIONAL TECTONICS OF THE UMBRIA-MARCHE BASIN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
We have determined the magnetostratigraphy in eight Upper Cretaceous to Eocene sedimentar y sections in the Umbria and Marche Region of the Northern Apennines, Italy. Paleomagnetic samples were collected at roughly 1 m intervals from the sections studied. Both alternating field and thermal demagnetization were carried out. Microfossils in the specimens were studied to facilitate identification of the magnetic polarity intervals. We have used the combined paleomagnetic and paleontological results in conducting a high—resolution correlation and in reconstructing the paleobasin tectonic history. The magnetostratigraphic results from this study contribute to the understanding of three aspects
Keywords: Magnetic stratigraphy; Scaglia Rossa; Upper Cretaceous—Eocene; Northern Apennine; Italy; Synsedimentary tectonic, Paleotopography.